A logical journey : from Gödel to philosophy - Wang, Hao, 1921- (Representation and mind., 1996)
Hao Wang (1921-1995) was one of the few confidants of the great mathematician and logician Kurt Godel. A Logical Journey is a continuation of Wang's Reflections on Kurt Godel and also elaborates on discussions contained in From Mathematics to Philosophy. A decade in preparation, it contains important and unfamiliar insights into Godel's views on a wide range of issues, from Platonism and the nature of logic, to minds and machines, the existence of God, and positivism and phenomenology. The impact of Godel's theorem on twentieth-century thought is on a par with that of Einstein's theory of relativity, Heisenberg's uncertainty principle, or Keynesian economics. These previously unpublished intimate and informal conversations, however, bring to light and amplify Godel's other major contributions to logic and philosophy. They reveal that there is much more in Godel's philosophy of mathematics than is commonly realized, and more in his philosophy than merely a philosophy of mathematics.